Antibacterial Activity of Ethyl Acetate Fraction of Passion Fruit Peel (Passiflora Edulis Sims) on Staphylococcus Aureus and Escherichia Coli - Nugraha, Sony Eka; Suryadi Achmad; Erly Sitompul (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
North Sumatera is one of the central areas of purple passion fruit production in Indonesia. Processing passion fruit into beverage products (passion fruit juice) produces peel has not been utilized. The use of passion fruit skin needs to be studied so that it can be useful as a raw material for antibacterial drug preparations. The aim of this study was to determine the phytochemical constituent screening and antibacterial activity of ethyl acetate fraction of purple passion fruit peel against Staphylococcus aureus and Escherichia coli. Simplicia and ethyl acetate fraction were determinated its phytochemical properties. The extraction process by percolation method using ethanol 96% and continue to fractionation process by liquid liquid extraction method using n-hexane and ethyl acetate. The antibacterial activity were tested against Staphylococcus aureus and Escherichia coli using agar diffusion method with paper discs. The result showed that the simplicia characteristic of passion fruit peel were water content of 8.64%, water soluble extract of 31.69%, ethanol soluble extract of 13.02%, ash total of 7.89%, and insoluble ash in acid of 0.816%. The phytochemical screening simplicia and ethyl acetate fraction showed the presence of flavonoids, glycosides, saponins and tannins. The antibacterial activity test showed that the ethyl acetate fraction has an effective inhibition at the concentration of 100 mg/ml against Staphylococcus aureus and Escherichia coli, it showed dose dependent manner. The ethyl acetate fraction of passion fruit peel (Passiflora edulis Sims) has an antibacterial activity on Staphylococcus aureus and Escherichia coli